2005
DOI: 10.1007/s11661-005-0287-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of crystallographic texture during high rate deformation of rolled and hot-pressed beryllium

Abstract: Weakly textured hot-pressed (HP) beryllium and strongly textured hot-rolled beryllium were compressed using a split-Hopkinson pressure bar (SHPB) (strain rate ϳ4500 s Ϫ1 ) to a maximum of 20 pct plastic strain as a function of temperature. The evolution of the crystallographic texture was monitored with neutron diffraction and compared to polycrystal plasticity models for the purpose of interpretation. The macroscopic response of the material and the active deformation mechanisms were found to be highly depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Thus, there was a higher contribution from the basal slip system to deformation in all four samples at the higher strain rate. The contribution of basal slip to room temperature deformation of low c/a metals like zirconium and titanium is considered minimal [2], with beryllium as an exception [33]. However, it has been reported that in spite of the fact that the CRSS for basal slip is higher than that for prismatic slip in titanium, basal slip can be activated [10, [34][35][36][37].…”
Section: Deformation Mode Activitymentioning
confidence: 99%
“…Thus, there was a higher contribution from the basal slip system to deformation in all four samples at the higher strain rate. The contribution of basal slip to room temperature deformation of low c/a metals like zirconium and titanium is considered minimal [2], with beryllium as an exception [33]. However, it has been reported that in spite of the fact that the CRSS for basal slip is higher than that for prismatic slip in titanium, basal slip can be activated [10, [34][35][36][37].…”
Section: Deformation Mode Activitymentioning
confidence: 99%
“…[27,28,69] The response of Ti 3 SiC 2 at room temperature is fully reversible until failure, i.e., there is no plastic deformation. Plastic deformation is only observed at temperatures higher than the brittle-toplastic transition, at which point the fracture toughness drops, but the strain to failure, due to cavitation and microcracking, is greatly enhanced.…”
Section: Damping and The Case Against Reversible Twinningmentioning
confidence: 99%
“…Of those tests that have been conducted to high strain rates most use either an unusual sample dimension [2], or a novel testing method which utilises a strain path that is not common in an industrial process, i.e., the split-Hopkinson pressure bar (SHPB) [5][6][7][8][9]. With these techniques it is possible to produce strain rates as high as 7000 s −1 [5,6].…”
Section: Introductionmentioning
confidence: 99%